(untitled) (Scientific journal of the Fergana State University, 2024)
The article is dedicated to the stages of development of intercultural pragmatics theory in linguistics. It examines the key stages and milestones in the formation of this discipline, from its inception in the mid-20th century to the present day. The main concepts and approaches proposed by leading scholars in the field of intercultural communication, such as speech act theory, the cooperative principle, politeness theory, and the concept of communicative strategies, are analyzed. Special attention is given to the influence of cultural differences on the pragmatic aspects of communication and how these differences affect the interpretation and perception of speech acts. Examples of intercultural studies that demonstrate the practical application of intercultural pragmatics theory in various contexts are considered. The work emphasizes the importance of considering cultural factors in linguistic analysis and offers prospects for further research in this area. The article will be useful for researchers, educators, and students interested in intercultural communication and pragmatics.